EVALUATION OF POSYANDU INFORMATION SYSTEMS USING THE HEALTH METRIC NETWORK MODEL - Maghfiroh, Sufi Aulia; Wulandari, Ratna Dwi (Universitas Airlangga, 2022)
Introduction: Posyandu has an important role in disseminating health information and monitoring the growth and development of infants and toddlers. The information generated serves as a material for consideration of decision-making. In order for the decision-making to be right on target, it is necessary to evaluate the Posyandu recording and reporting system. The purpose of this study is to assess the implementation of the Putra Bangsa Posyandu recording and reporting system in Bojonegoro which is more commonly referred as Posyandu Information System (PIS). Methods: used in this study is a qualitative approach that is presented descriptively using in-depth interviews and observation methods without making any intervention on the target. The Posyandu Information System Assessment uses Health Metrics Network components which are grouped into 3 parts, namely input, process, and output. Result: of the evaluation of the implementation of the Posyandu Information System at Putra Posyandu show that in terms of input the implementation of the Posyandu Information System is not in accordance with the guidelines for implementing the Posyandu Information System. From the aspect of the process it was found that data collection had been carried out routinely, but there was one format that was not yet routine. In terms of output it shows that the data generated are quite complete but not timely. Conclusion: Human Resources (HR) is one of the most dominant factors causing Posyandu Information Systems not to run optimally. The results of this study can help Health Information Management in improving the Posyandu Information System.